“Just whack it on until it gets hot”: working with IoT data in the home - Fischer, Joel E.; Crabtree, Andy; Rodden, Tom; Colley, James A.; Costanza, Enrico; Jewell, Michael O.; Ramchurn, Sarvapali D. (2016)
This paper presents findings from a co-design project that aims to augment the practices of professional energy advisors with environmental data from sensors deployed in clients’ homes. Premised on prior ethnographic observations we prototyped a sensor platform to support the work of tailoring advice-giving to particular homes. We report on the deployment process and the findings to emerge, particularly the work involved in making sense of or accounting for the data in the course of advice-giving. Our ethnomethodological analysis focuses on the ways in which data is drawn upon as a resource in the home visit, and how understanding and advice-giving turns upon unpacking the indexical relationship of the data to the situated goings-on in the home. This insight, coupled with further design workshops with the advisors, shaped requirements for an interactive system that makes the sensor data available for visual inspection and annotation to support the situated sense-making that is key to giving energy advice.